A Novel Mouse Model of Acute‐on‐Chronic Cholestatic Alcoholic Liver Disease: A Systems Biology Comparison With Human Alcoholic Hepatitis. (28th November 2019) - Furuya, Shinji; Argemi, Josepmaria; Uehara, Takeki; Katou, Yuuki; Fouts, Derrick E.; Schnabl, Bernd; Dubuquoy, Laurent; Belorkar, Abha; Vadigepalli, Rajanikanth; Kono, Hiroshi; Bataller, Ramon; Rusyn, Ivan
Abstract : Background: Alcohol‐related liver disease is the main cause of liver‐related mortality worldwide. The development of novel targeted therapies for patients with advanced forms (i.e., alcoholic hepatitis, AH) is hampered by the lack of suitable animal models. Here, we developed a novel mouse model of acute‐on‐chronic alcohol liver injury with cholestasis and fibrosis and performed an extensive molecular comparative analysis with human AH. Methods: For the mouse model of acute‐on‐chronic liver injury, we used 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine (DDC, 0.05% w/w) diet for 8 weeks to establish cholestatic liver fibrosis. After 1‐week washout period, male mice were fed intragastrically for 4 weeks with up to 24 g/kg of ethyl alcohol in a high‐fat diet. This animal model was phenotyped using histopathology, clinical chemistry, microbiome, and gene expression approaches. Data were compared to the phenotypes of human alcohol‐related liver disease, including AH. Results: Mice with cholestatic liver fibrosis and subsequent alcohol exposure (DDC + EtOH) exhibited exacerbated liver fibrosis with a pericellular pattern, increased neutrophil infiltration, and ductular proliferation, all characteristics of human AH. DDC administration had no effect on urine alcohol concentration or liver steatosis. Importantly, DDC‐ and alcohol‐treated mice showed a transcriptomic signature that resembled that of patients with AH. Finally, we show that mice in the DDC + EtOH group had an increased gut barrier dysfunction, mimicking an important pathophysiological mechanism of human AH. Conclusions: We developed a novel mouse model of acute‐on‐chronic cholestatic alcoholic liver injury that has considerable translational potential and can be used to test novel therapeutic modalities for AH. Abstract : This work is improving on existing animal models of alcohol‐induced liver injury, especially advanced forms of alcoholic hepatitis (AH). We compared the mouse model of liver fibrosis and intragastric alcohol administration to various forms of human ASH/AH based on a recently published study in human AH (Argemi et al . Nat Commun . 2019;10(1):3126. doi: https://doi.org/10.1038/s41467-019-11004-3, PMID: 31311938).